2016
DOI: 10.4049/jimmunol.1600210
|View full text |Cite
|
Sign up to set email alerts
|

The Complement C3a Receptor Contributes to Melanoma Tumorigenesis by Inhibiting Neutrophil and CD4+ T Cell Responses

Abstract: The complement peptide C3a is a key component of the innate immune system and a major fragment produced following complement activation. We used a murine model of melanoma (B16-F0) to identify a hitherto unknown role for C3a–C3aR signaling in promoting tumor growth. The results show that the development and growth of B16-F0 melanomas is retarded in mice lacking C3aR, whereas growth of established melanomas can be arrested by C3aR antagonism. Flow cytometric analysis showed alterations in tumor-infiltrating leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 50 publications
(35 reference statements)
6
65
0
2
Order By: Relevance
“…Improved disease outcome in C3aR −/− mice has been observed in a model of melanoma; tumorigenesis was associated with increased numbers of neutrophils and a pro-inflammatory tumour microenvironment 77 . The deleterious role of neutrophils in cancer has been further confirmed in a model of spontaneous intestinal tumorigenesis in mice with a mutation in the adenomatous polyposis coli ( Apc ) gene (that is, Apc Min /+ mice).…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 86%
“…Improved disease outcome in C3aR −/− mice has been observed in a model of melanoma; tumorigenesis was associated with increased numbers of neutrophils and a pro-inflammatory tumour microenvironment 77 . The deleterious role of neutrophils in cancer has been further confirmed in a model of spontaneous intestinal tumorigenesis in mice with a mutation in the adenomatous polyposis coli ( Apc ) gene (that is, Apc Min /+ mice).…”
Section: Feeding Inflammation and Tumorigenesismentioning
confidence: 86%
“…The tested mouse tumor models include TC-1 cervical cancer, Lewis lung cancer, RMA lymphoma, 4T1, and E0771 breast cancer, B16 melanoma, HPV16 skin cancer, and MC38 colon cancer with either transplanted tumor cells or spontaneously developed cancers. Complement signaling was disrupted in these animal studies by using genetic models including mice deficient for C3, C4, C3aR, or C5aR1 (4,(9)(10)(11)(12)(13)(14)(15) or inhibitors to complement C3, C3aR, and C5aR1 (4-6, 8, 10-12, 14). The reported results are highly consistent in that tumor growth is suppressed when complement-mediated signaling is inhibited or removed.…”
Section: Complement Suppresses Antitumor Immunity Through C3ar and C5armentioning
confidence: 99%
“…It was reported that tumor or circulating complement levels are positively correlated with tumor size and poor outcome in different types of cancers, such as neuroblastoma, colorectal, lung, ovarian cancer, chronic lymphocytic leukemia, and carcinomas of the digestive tract (3). Extensive animal studies have also demonstrated that the complement system functions to inhibit antitumor immunity (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Mechanistically, complement may inhibit antitumor immunity by promoting recruitment of myeloid-derived suppressor cells (MDSCs) into the tumor microenvironment (TME) (4-6, 9, 12, 13) or by suppressing dendritic cells (DCs)/NK cell activation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Dans le modèle murin de mélanome, la délétion du gène codant le récepteur du C3a, le C3aR [30], ou une déficience en C3 [31], sont à l'origine d'une croissance tumorale ralentie qui est associée à un remodelage du microenvironnement immunitaire. Cela se traduit par…”
Section: Protéines Du Complément Et Contexte Tumoralunclassified